Tamoxifen and bone morphogenic protein-7 modulate fibrosis and inflammation in the peritoneal fibrosis model developed in uremic rats - Filipe M. O. Silva; Elerson C. Costalonga; Cleonice Silva; Ana C. O. Carreira; Samirah A. Gomes; Mari C. Sogayar; Camilla Fanelli; Irene L. Noronha (BMC, 2019)
Abstract Background Peritoneal fibrosis (PF) represents a long-term complication of peritoneal dialysis (PD), affecting peritoneal membrane (PM) integrity and function. Understanding the mechanisms underlying PF development in an uremic environment aiming alternative therapeutic strategies for treating this process is of great interest. The aim of this study was to analyze the effects of tamoxifen (TAM) and recombinant BMP7 (rBMP7) in an experimental model of PF developed in uremic rats. Methods To mimic the clinical situation of patients on long-term PD, a combo model, characterized by the combination of PF and CKD with severe uremia, was developed in Wistar rats. PF was induced by intraperitoneal (IP) injections of chlorhexidine gluconate (CG), and CKD was induced by an adenine-rich diet. Uremia was confirmed by severe hypertension, increased blood urea nitrogen (BUN> 120 mg/dL) and serum creatinine levels (> 2 mg/dL). Uremic rats with PF were treated with TAM (10 mg/Kg by gavage) or BMP7 (30 μg/Kg, IP). Animals were followed up for 30 days. Results CG administration in uremic rats induced a striking increase in PM thickness, neoangiogenesis, demonstrated by increased capillary density, and failure of ultrafiltration capacity. These morphological and functional changes were blocked by TAM or rBMP7 treatment. In parallel, TAM and rBMP7 significantly ameliorated the PM fibrotic response by reducing α-SMA, extracellular matrix proteins and TGF-ß expression. TAM or rBMP7 administration significantly inhibited peritoneal Smad3 expression in uremic rats with PF, prevented Smad3 phosphorylation, and induced a remarkable up-regulation of Smad7, an intracellular inhibitor of TGFβ/Smad signaling, contributing to a negative modulation of profibrotic genes. Both treatments were also effective in reducing local inflammation, possibly by upregulating IκB-α expression in the PM of uremic rats with PF. In vitro experiments using primary peritoneal fibroblasts activated by TGF-ß confirmed the capacity of TAM or rBMP7 in blocking inflammatory mediators, such as IL-1ß expression. Conclusions In conclusion, these findings indicate important roles of TGF-ß/Smad signaling in PF aggravated by uremia, providing data regarding potential therapeutic approaches with TAM or rBMP7 to block this process.